PERKUATAN GESER BALOK BETON BERTULANG MENGGUNAKAN GLASS FIBER REINFORCED POLYMER (GFRP) - Deskarta, Putu (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 2 Juli 2009)
In order to know the effect of GFRP plates on increasing capacity of reinforced concrete beams, an experiment on reinforced concrete beams strengthened by GFRP plates is made. This experiment is focused on finding the effects of bounding GFRP plates to the side surfaces of the beams on increasing capacity of the beams. In this experiment the effect of adding GFRP plates having fiber directions of 00/900, ±450 and 00 to the increasing shear capacity of reinforced concrete section was studied. The beams had section dimension of 100 cm by 150 cm and length 950 cm. The GFRP plates were added on the two side surfaces of the beams by covering the surfaces with epoxy resin and then add glass fiber in the form of woven roving in the direction needed and finally cover again with the epoxy. The beams were simply supported and subjected to four points load. Data recorded were the load-deflection at every step of loading until failure and modes of failure of the beams. The result shows that the beams without GFRP fail in shear failure mode and the beams with GFRP fail in flexural failure mode. More over, addition of GFRP to the beams increases the load capacity of the beams by 12.48% averagely. The fiber direction gives a slight difference to the increasing capacity and the amount of the increasing capacity given by the fiber direction of 0o/90o, 0o, and ±45o are 13.744%, 11.374%, and 12.322% respectively. Theoretically the fiber direction of ±45o should gives the highest value, but this is not happen because of de-bounding of the GFRP plate from the surface of the beams.
Keywords: GFRP plates, fiber directions, and reinforced concrete beams.